Investigating mitochondrial uncoupling protein 1 and leptin in the interplay of metabolic adaptation and inflammatory response of dairy cows during the peripartum period - Arfuso, Francesca; Arrigo, Federica; Rizzo, Maria; Sisia, Giulia; Fiore, Enrico; Giannetto, Claudia; Liotta, Luigi; Piccione, Giuseppe; Lopreiato, Vincenzo (Frontiers in Veterinary Science, 2025)
IntroductionThis study investigated key metabolic markers and inflammatory responses in Simmental cows during the peripartum period, a physiologically demanding phase marked by metabolic and immune adjustments.Materials and methodsTen Simmental cows were monitored, and blood samples were collected at various stages surrounding calving. Plasma concentrations of leptin, mitochondrial uncoupling protein 1 (UCP1), glucose, non-esterified fatty acids (NEFA), triglycerides, total cholesterol, β-OH-butyric acid (BHB), interleukin (IL)-1β, IL-6, and tumor necrosis factor α (TNFα) were measured.ResultsResults indicated a decline in UCP1 from prepartum to calving, followed by a rise until three weeks postpartum. Leptin levels decreased prepartum and stabilized post-calving. IL-6 peaked at −7 days, while TNFα was elevated at −21 and −7 days compared to calving and subsequent days. Glucose levels were higher at −21 and −7 days, and NEFA increased from −21 until calving, then decreased. Total cholesterol was lower at calving and one day postpartum compared to earlier and later measurements. Triglycerides were elevated prepartum but decreased at calving. Leptin showed a positive correlation with TNFα, glucose, and triglycerides, and a negative correlation with NEFA. UCP1 values were negatively correlated with NEFA and positively correlated with total cholesterol.DiscussionThese findings highlight the complex metabolic adjustments during the peripartum period in dairy cows. The observed fluctuations in UCP1 and leptin, along with their correlations with inflammatory and metabolic parameters, underline the intricate interplay between energy metabolism and immune function during this critical transition phase.